Survival Outcomes of Cardiopulmonary Resuscitation in the Patients Diagnosed with Chronic Kidney Disease - Niaz Hussain Abassi, Qazi Talal Ali, Bushra Gohar Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The essential part of medical care for the patients diagnosed with the chronic kidney diseases (CKD) is resuscitation. The limited and sufficient knowledge about the outcomes of cardiopulmonary resuscitation is present. Objective: The study aimed to measure the survival outcomes of the cardiopulmonary resuscitation in the patients diagnosed with CKD. Study design: This observational study was conducted at the Al Nafees Medical College and Hospital Islamabad and Sahara Medical College, Narowal from March 2021 to March 2022. Material and Methods: The study was conducted on 200 patients visited the cardiology department of our institute teaching hospital. The patients older than 18 years were included in the study. The demographic features with survival outcomes were recorded. The t-test and chi-square test was performed for the statistical analysis. The regression model was used to identify the relationship between CKD and in-hospital mortality cases. The model was also adjusted. Results: It was noted that all the patients suffering from CKD were of old age and most of them belongs from those area that was not facilitate with proper medical care and other facilities. All these diseases were also present in the patients with CDK. Most of the patients had age more than 76 years but the mortality rate of the CDK patients was higher in the young patients suffering from CDK. But after justification of all the other symptoms it was predicted that the rate of mortality is 10 % higher in older patients. Conclusion: it was concluded that the mortality rate is greater in the patients having some serious illness in the hospital like CPR. After receiving CPR, the conditions of older patients get worst. The purpose of this study was to provide information to the patients suffering from CKD and the medical staff treating them. Keywords: Chronic kidney disease, mortality rates, cardiopulmonary resuscitation, advance care and cardiovascular disease.